Technical efficiency of establishments in Malaysia’s electrical and electronics industries: exporting or vertical trade? - Noor Aini Khalifah; Zakiah Jaafar (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study compares export intensity and vertical trade intensity in determining technical efficiency (TE) of establishments in Malaysia’s electrical and electronics industries (E&E) amongst other explanatory variables. We measure fragmentation or vertical trade intensity as two-way trade or the overlap of exports and imported inputs weighted by gross output of establishments. In the overall sample of establishments, vertical trade intensity is a significant determinant of (TE) whereas export intensity is not. A bigger scale of production, a higher degree of vertical integration and higher labour quality are positively related to TE whereas higher industrial concentration is negatively associated with TE. In the sub-sample of ordinary trading establishments, export intensity is a significant determinant of technical efficiency whereas in the sub-sample of vertical trading establishments, export intensity is not a significant determinant of TE. Higher export intensity does not necessarily mean higher efficiency of establishments and hence, an unqualified policy of export expansion within the context of vertical trade and global value chains in production should be conducted with caution. Technical progress is not significant in all of the models estimated.